2018
DOI: 10.1080/10400435.2018.1457574
|View full text |Cite
|
Sign up to set email alerts
|

Perceived importance and difficulty of online activities among visually impaired persons in Nigeria

Abstract: This study investigated perceived relevance of and difficulties in access to day-to-day online activities among visually impaired computer users who used screen readers. The 98 participants in the study were grouped into visually impaired adults (aged 20-59, n = 60) and visually impaired older adults (aged 60 and over, n = 38). Data were collected in structured interview questionnaires with Likert scales exploring ratings of perceived importance and difficulty of access to 11 online platforms of various intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Several studies have investigated the basic ICT skills and ICT usage of individuals with VI (Haneefa & Syamili, 2014 ; Şimşek et al, 2010 ; Soman & Sudhier, 2015 ; Yılmaz, 2019 ), their technological needs (Fuglerud, 2011 ), as well as the challenges they face related to technology access (Thongma-eng, 2015 ), and the related importance of these technologies (Ashraf et al, 2017 ; Douglas, 2001 ; Kumar & Sanaman, 2013 ; Okonji et al, 2020 ). These studies have revealed that individuals with VI can perform basic computer skills such as preparing documents, searching for information using the Internet, as well as sending emails and communicating with friends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the basic ICT skills and ICT usage of individuals with VI (Haneefa & Syamili, 2014 ; Şimşek et al, 2010 ; Soman & Sudhier, 2015 ; Yılmaz, 2019 ), their technological needs (Fuglerud, 2011 ), as well as the challenges they face related to technology access (Thongma-eng, 2015 ), and the related importance of these technologies (Ashraf et al, 2017 ; Douglas, 2001 ; Kumar & Sanaman, 2013 ; Okonji et al, 2020 ). These studies have revealed that individuals with VI can perform basic computer skills such as preparing documents, searching for information using the Internet, as well as sending emails and communicating with friends.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed that individuals with VI can perform basic computer skills such as preparing documents, searching for information using the Internet, as well as sending emails and communicating with friends. In their study, Okonji et al ( 2020 ) suggested that the sending and reading of emails, online banking, online shopping, and seeking online health information are considered the most important as well as the most difficult online activities for adults with VI to perform.…”
Section: Introductionmentioning
confidence: 99%
“…Okonji et al (2020) elucidated that screen readers convert text-to-speech and along with a computer, audio devices such as headphones or earphones and with the assistance of a librarian, several electronic books and electronic journals can be accessed conveniently (Sutar, 2019). Academic libraries worldwide are found to be lacking in providing suitable forms of resources and services.…”
Section: Review Of Literaturementioning
confidence: 99%